Genetic Landscape of SH3TC2 variants in Russian patients with Charcot–Marie–Tooth disease - Shchagina, Olga; Murtazina, Aysylu; Chausova, Polina; Orlova, Mariya; Dadali, Elena; Kurbatov, Sergei; Kutsev, Sergey; Polyakov, Aleksander (Frontiers in Genetics, 2024)
Charcot-Marie-Tooth disease type 4C (CMT4C) OMIM#601596 stands out as one of the most prevalent forms of recessive motor sensory neuropathy worldwide. This disorder results from biallelic pathogenic variants in the SH3TC2 gene. Within a cohort comprising 700 unrelated Russian patients diagnosed with Charcot-Marie-Tooth disease, we conducted a gene panel analysis encompassing 21 genes associated with hereditary neuropathies. Among the cohort, 394 individuals exhibited demyelinating motor and sensory neuropathy. Notably, 10 cases of CMT4C were identified within this cohort. The prevalence of CMT4C among Russian demyelinating CMT patients lacking the PMP22 duplication is estimated at 2.5%, significantly differing from observations in European populations. In total, 4 novel and 9 previously reported variants in the SH3TC2 gene were identified. No accumulation of a major variant was detected. Three previously reported variants, c.2860C>T p.(Arg954*), p.(Arg658Cys) and c.279G>A p.(Lys93Lys), recurrently detected in unrelated families. Nucleotide alteration p.(Arg954*) is present in most of our patients (30%).